Semiotic Analysis Of The Motivational Message In The Lyrics Of The Song "Good Days" By Sza - Menza , Noval Nabadi Sevi; Hariyanto, Didik (Procedia of Social Sciences and Humanities, 2024)
This research aims to analyze the message contained in the song "Good Days" by SZA using Ferdinand de Saussure's semiotic theory. The phenomenon addressed in this song is the importance of maintaining a positive mindset and continuous efforts to achieve happiness amidst life's challenges. The method used in this research is semiotic analysis, focusing on the denotative and connotative meanings conveyed through the song's lyrics. The analysis results indicate that the song's denotative meaning reflects an ongoing effort to achieve success, while its connotative meaning emphasizes that true happiness comes from within, through a positive mindset and mental resilience. The song also reveals the myth that happiness is not determined by external factors but originates from within oneself. In conclusion, "Good Days" serves as a powerful motivational medium, encouraging listeners to adopt a positive mindset, appreciate small moments of happiness, and build resilience in facing life's challenges.